RIVALITAS EL CLASICCO DAN PEMBENTUKAN IDENTITAS SOSIAL (STUDI TENTANG PERTARUNGAN WACANA ANTAR SUPORTER SEPAKBOLA DI JEJARING SOSIAL) (Forum Ilmu Sosial, 2012)
Self-identity is a reflection of socially constructed culture related to race, class, gender, sexuality, history and power. Development of information technology is so rapid that affect the process of identity formation is not only derived from the real world but also derived from the virtual world. This paper aims to analyze the formation of social identity through social networking facebook. The battle of two big European clubs, the Real Madrid vs Barcelonan in the game El Clasicco, make to fight the discourse between the two clubs football fans are. By utilizing facebook media, fans of these two football clubs are mutually exhibitting their identity in cyberspace. Visual identity is projected to represent identity in the real world. That way, identity is important because it can make a person entered or categorized into a particular group.